Epidemiological profile of women with gynecological cancer in brachytherapy: a cross-sectional study - Rosa,Luciana Martins da (2021)
ABSTRACT Objective: to analyze the sociodemographic and clinical profile of women with gynecological cancer in brachytherapy. Method: a cross-sectional study including records of 1,930 visits of women in brachytherapy assisted between 2006-2016 in Santa Catarina (Brazil). Collection was performed in 2019, in an institutional bank, submitted to frequency measurements, chi-square test, 95% confidence intervals, significance level of 0.05. Results: women aged 40-59 years (47.2%), white (93.3%); with elementary school (65%); cervical cancer (78.5%); stages II-III (73.3%) figured prominently. In the comparison of staging proportions in the topography variable, a higher proportion of malignant neoplasm of cervix uteri unspecified in the grouped III-IV staging (84.6%). Conclusion: the profile analysis shows the need for screening and health education for prevention and/or early detection of gynecological cancers and training of nurses specialized in radiotherapy to care for women’s health.